Ecologically different earthworm species are the driving force of microbial hotspots influencing Pb uptake by the leafy vegetable Brassica campestris - Tibihenda, Cevin; Zhong, Hesen; Liu, Kexue; Dai, Jun; Lin, Xiaoqin; Motelica-Heino, Mikael; Hou, Shuyu; Zhang, Menghao; Lu, Ying; Xiao, Ling; Zhang, Chi (Frontiers in Microbiology, 2023)
This study highlights the importance of two ecologically different earthworm species ( Amynthas aspergillum and Eisenia fetida) as the driving force of microbial hotspots to enhance Pb accumulation in the leafy vegetable Brassica campestris at different Pb contamination levels . The fingerprints of phospholipid fatty acids (PLFAs) were employed to reveal the microbial mechanism of Pb accumulation involving earthworm-plant interaction, as PLFAs provide a general profile of soil microbial biomass and community structure. The results showed that Gram-positive (G + ) bacteria dominated the microbial community. At 0 mg•kg -1 Pb, the presence of earthworms significantly reduced the total PLFAs. The maximum total PLFAs was found at 100 mg•kg -1 Pb with E. fetida inoculation.A significant shift in the bacterial community was observed in the treatments with E. fetida inoculation at 500 and 1000 mg•kg -1 Pb, where the G + /G -bacteria ratio was significantly decreased compared to no earthworm inoculation. Principal component analysis (PCA) showed that E. fetida had a greater effect on soil microbial hotspots than A. aspergillum, thus having a greater effect on the Pb uptake by B. campestris. Redundancy analysis (RDA) showed that soil microbial biomass and structure explained 43.0% (R 2 = 0.53) of the total variation in Pb uptake by B. campestris, compared to the 9.51% of microbial activity. G -bacteria explained 23.2% of the total variation in the Pb uptake by B. campestris, significantly higher than the other microbes.The Mantel test showed that microbial properties significantly influenced Pb uptake by B. campestris under the driving force of earthworms. E. fetida inoculation was favorable for the G - bacterial community, whereas A. aspergillum inoculation was favorable for the fungal community. Both microbial communities facilitated the entry of Pb into the vegetable food chain system. This study delivers novel evidence and meaningful insights into how earthworms prime the microbial mechanism of Pb uptake by leafy vegetables by influencing soil microbial biomass and community composition. Comprehensive metagenomics analysis can be employed in future studies to identify the microbial strains promoting Pb migration so as to develop effective strategies to mitigate Pb contamination of food chains.